The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.14233/ajchem.2019.22238
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanoparticles using Salacca zalacca Extract as Reducing Agent and It’s Antibacterial Activity

Abstract: In this article, the synthesis of silver nanoparticles through a reduction reaction process using Salacca zalacca extract is reported. The AgNPs were characterized using X-ray diffraction, transmission electron microscopy, Fourier transform infrared and UV-visible spectrophotometry methods. The AgNPs antibacterial activity was determined against of Gram-positive bacteria (Staphylococcus epidermidis) and Gram-negative bacteria (Escherichia coli). The main functional groups contained in Salacca zalacca extract a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 42 publications
0
0
0
1
Order By: Relevance
“…Preparation of Snake fruit Peel Extract (SPE) AgNPs (Prodjosantoso et al, 2019) A total of 150 mL of the extract was added sequentially with AgNO3 solution (0.25 mM, 1.00 mM, 2.00 mM, and 4.00 mM) dropwise until the color turned more intense in a water bath at 30 0 C, 50 0 C, and 75 0 C and incubated for 15, 30, 60, 120, 240, and 1440 minutes before covering with aluminium foil.…”
Section: Identification Of Polyphenolmentioning
confidence: 99%
See 3 more Smart Citations
“…Preparation of Snake fruit Peel Extract (SPE) AgNPs (Prodjosantoso et al, 2019) A total of 150 mL of the extract was added sequentially with AgNO3 solution (0.25 mM, 1.00 mM, 2.00 mM, and 4.00 mM) dropwise until the color turned more intense in a water bath at 30 0 C, 50 0 C, and 75 0 C and incubated for 15, 30, 60, 120, 240, and 1440 minutes before covering with aluminium foil.…”
Section: Identification Of Polyphenolmentioning
confidence: 99%
“…This research followed the procedure reported by (Prodjosantoso et al, 2019) with modifications and AgNPs were synthesized using a volume ratio of 2:15 (20 mL) AgNO3 to 150 mL SPE as reducing and capping agents. In this context, the incubation procedure was carried out in a closed container in a dark room.…”
Section: Synthesis Optimization Of Silver Nanoparticles From Spementioning
confidence: 99%
See 2 more Smart Citations
“…Klaster 3 ditunjukkan dengan simpul berwarna biru (Gambar 5) dengan kata kunci terdiri dari "e. coli", "nanoparticlesa", dan "silver". Klaster ini fokus pada uji aktifitas antibakateri NP-Ag yang disintesis menggunakan agen bio-reduksi yang diperoleh dari tumbuhan Indonesia diantaranya Impatiens balsamina dan lantana camara [21], Salacca zalacca [22], Diospyros discolor Willd [23], dan Scaevola frutescen (Mill.) Krause [24].…”
Section: Analisis Kontenunclassified